Experience of Asthma Patients in Management of Asthmatic Status - Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus; Wijaya, Andra Saferi (JOSING: Journal of Nursing and Health, 2024)
This study aims to determine the experience of asthma sufferers in managing status asthmaticus. This research design uses a qualitative phenomenological study approach. The results of this research obtained 3 (three) aspects, namely the knowledge aspect of participants knowing that asthma is characterized by shortness of breath, wheezing, coughing and difficulty breathing, which is caused by allergies and hereditary factors. In the psychological aspect, the impact of the attack was felt by participants as anxious, silent, pain in the lungs and shortness of breath. In the aspect of home management during a recurrence, namely taking medication, spraying an inhaler, if it doesn't resolve, take him to the hospital. In conclusion, the experience of asthma sufferers in managing asthma in the knowledge aspect is good status, the psychological aspect of the impact of attacks is felt by anxiety and in the management aspect they have taken initial action during a relapse. Keywords: Experience, Management, Status Asthmaticus